Your first answer is wrong.
The area should be:
a= 65
b= 109
The second one is probably C.)
Let us assume the total number of bowls of cereal that Nathan has eaten in a year = x
With each bowl of cereal, Nathan has 1/18 gallon of Milk.
In total the number of gallons of mulk in a year = 8 gallons,
Therefore, we frame the equation as shown below to calculate "x"
1/18 * x = 8
x = 18*8 = 144
Number of bowls of cereal Nathan ate in a year = 144 bowls
In the aerobics classes of 4 will the cost for members and nonmember be the same.
What is an expression?
Mathematical expression is defined as the collection of the numbers variables and functions by using operations like addition, subtraction, multiplication, and division.
Given that;
At a local fitness center, members pay an $8 membership fee and $4 for each aerobic class.
And, Nonmembers pay $6 for each aerobic class.
Now,
We can formulate;
For members, the cost = $8 + 4x
Where, x is the aerobic class.
For nonmembers;
The cost = 6x
We can equate both the equation, we get;
6x = 8 + 4x
Solve for x as;
6x - 4x = 8
2x = 8
x = 4
Thus, In the aerobics classes of 4 will the cost for members and nonmember be the same.
Learn more about the mathematical expression visit:
#SPJ2
Answer: 15.12
Step-by-step explanation:
84% of 18
=84/ 100 × 18
=84× 18 / 100
=1512/100
=15.12
The original price is $15.12
The number 81.54 is 107.99% percentage of 75.5
We have,
To find what percent of 75.5 is 81.54, we can use the following formula:
(81.54 / 75.5) * 100
Step 1: Divide 81.54 by 75.5:
81.54 / 75.5 ≈ 1.0799
Step 2: Multiply the result by 100 to convert it to a percentage:
1.0799 * 100 ≈ 107.99
Therefore, 81.54 is approximately 107.99% of 75.5.
To explain it further, if we consider 75.5 as the whole or 100%, then 81.54 is approximately 107.99% of that whole value.
Thus,
In other words, 81.54 represents about 107.99% of 75.5.
Learn more about percentages here:
#SPJ6
Answer:
Step-by-step explanation:
the expression we have is:
to solve we need to develop the square binomial
with the following formula:
So we have:
and the expression now is:
developing multiplications to remove parentheses:
joining like terms:
This expression can be simplified so it becomes:
(3x^2 - 4) - (2x - 1)
3x^2 - 2x - 3
B) 592.5 - 1/80x
C) 600x - 1/80
D) 600 - 1/80x